PROBLEM REWINDYKACJI W II RZECZYPOSPOLITEJ DÓBR OBJĘTYCH KONFISKATĄ PO POWSTANIU STYCZNIOWYM PRZEZ RZĄDY CARSKIE - Starzec, Bartłomiej (Zeszyty Prawnicze, 2017)
The Problem of Recovery Property under Seizure by the Tsarist Government after the January Uprising in 1863 Year Summary Article describe a problem of recovery property under seizure by the tsarist government after the January Uprising in 1863 year. Confiscation of property was the penalty applicable to the participants and supporters of the uprising. The Russian government has applied it to every Polish independence uprising. Particularly confiscation of property was the negative consequences for the Polish gentry. Confiscation of property meant for the Polish gentry the social degradation. After regaining independence, Polish politicians have taken a series of attempts aimed at recovering stolen property. In 4-th may 1920 year the Polish parliament adopted a resolution in which the confiscation were considered acts of violence and lawlessness. However, still lacked a comprehensive act governing return of the property. In the case omission of the legislature, heirs of the insurgents began to assert their rights in courts. In the late twenties, the Supreme Court repeatedly upheld the claims for reimbursement of property. Enactment in 1932 year the law about recovery of property ended processes. Article describe problem of legal continuity between the first and second Polish Republic too.